Towards multifunctional coating in the boron-doped graphene/copper system. (May 2017) - Cantatore, Valentina; Panas, Itai
Abstract: A route to achieve multi-functional graphene coating is explored. Chemical bonding between copper substrate and coating results if the graphene is a priori boron doped. After pair-wise binding of boron sites to the Cu(111) surface, co-existence of pseudo-gap property in the graphene subsystem and a metallic density of states in the Cu subsystem at the common Fermi energy emerges. Apparently a paradox is that the two subsystems preserve and even recover their individual integrities upon formation of surface chemical bonds. Sensor capabilities are inferred. Employing pyridine as test molecule, conditioned ability of a nucleophile to offer competitive dative bonding, with the sub-strate, for boron sites is demonstrated. It is shown to occur for the case of half coverage and for adsorption to boron atoms originally bound to the on-top site on Cu(111). The ability of complementary boron sites to compensate for loss of binding between on-top site and boron, resulting from said bonding to the incoming nucleophile, is emphasized. Multifunctional substrate-coating system for catalysis as well as enhanced sensitization is inferred. Graphical abstract: